STRATEGI PENGEMBANGAN KAMPUNG ANGGREK DI AREA WISATA BIRDWATCHING ISYO HILLS RHEPANG MUAIF, NIMBOKRANG, JAYAPURA - Verena Agustini; Supeni Sufaati; Suharno Suharno (LPPM Uncen, 2021)
Orchid is a large group of flowering plants because of the beauty colourful flowers. This plant has high biodiversity in Papua, including in Jayapura Regency. The uniqueness of this plant attracts the attention of many researchers, collectors, and hobiis of this ornamental plants throughout the world. The purpose of this activity is to develop a strategy for introducing orchids species of Isyo Hills Birdwatching Ecotourism in Rhepang Muaif to the visitors. The activities were done by forum discussion group, practises on growing and caring orchids and build a screen house to display the collections. The result of the program showed that the community was very enthusiastic in following and understanding the importance of potential local orchids. Natural orchids in the Muaif Rhepang forest are quite high and are available throughout the year. The existence of a screen house is expected to be able to increase the orchids collection from the forest surrounding.Keywords: orchids species screen houses: collections; Nimbokrang; Jayapura